2020
DOI: 10.1038/s41526-020-00117-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular deconditioning during long-term spaceflight through multiscale modeling

Abstract: Human spaceflight has been fascinating man for centuries, representing the intangible need to explore the unknown, challenge new frontiers, advance technology, and push scientific boundaries further. A key area of importance is cardiovascular deconditioning, that is, the collection of hemodynamic changes—from blood volume shift and reduction to altered cardiac function—induced by sustained presence in microgravity. A thorough grasp of the 0G adjustment point per se is important from a physiological viewpoint a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 55 publications
4
69
0
Order By: Relevance
“…Moreover, their CVP value in microgravity is lower than in upright and supine position. Trend of our model results in different conditions is in very good agreement with this and other literature data 2 , 18 , 21 , 26 , 33 35 , 51 . Moreover, simulated CVP in HDT is higher than in microgravity 53 , 54 ; this result suggests that the upright fluid shift does not contribute to CVP reduction in microgravity, while the gravitational unloading of the P TW plays a key role.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, their CVP value in microgravity is lower than in upright and supine position. Trend of our model results in different conditions is in very good agreement with this and other literature data 2 , 18 , 21 , 26 , 33 35 , 51 . Moreover, simulated CVP in HDT is higher than in microgravity 53 , 54 ; this result suggests that the upright fluid shift does not contribute to CVP reduction in microgravity, while the gravitational unloading of the P TW plays a key role.…”
Section: Resultssupporting
confidence: 92%
“…Gallo et al reported 5.1% reduction for simulated CVP, in accordance with observed early spaceflights data 21 , 26 . Simulated CVP in microgravity condition shows a slight decrease (7.6%) with respect to the simulation in supine position on Earth.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations